2016
DOI: 10.18632/oncotarget.7342
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of TEF3-1 promotes cell cycle progression and angiogenesis in cancer

Abstract: TEF3-1 (transcriptional enhancer factor 3 isoform 1), also known as TEAD4 (TEA domain family member 4), was recently revealed as an oncogenic character in cancer development. However, the underlying molecular pathogenic mechanisms remain undefined. In this paper, we investigated nuclear TEF3-1 could promote G1/S transition in HUVECs, and the expression levels of cyclins and CDKs were upregulated. Additionally, if TEF3-1 was knocked down, the expression of cyclins and CDKs was downregulated while the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We have also revealed that E6-mediated upregulation of A3B is primarily caused by increased levels of TEAD1/4. A3B and TEAD1/4 are reported to be upregulated in various types of human cancer, and each has been proposed to play important roles in carcinogenesis (5)(6)(7)(8)(9)(28)(29)(30)(31)(32). This study thus establishes a novel transcriptional link between these oncogenic factors.…”
Section: Discussionmentioning
confidence: 55%
“…We have also revealed that E6-mediated upregulation of A3B is primarily caused by increased levels of TEAD1/4. A3B and TEAD1/4 are reported to be upregulated in various types of human cancer, and each has been proposed to play important roles in carcinogenesis (5)(6)(7)(8)(9)(28)(29)(30)(31)(32). This study thus establishes a novel transcriptional link between these oncogenic factors.…”
Section: Discussionmentioning
confidence: 55%
“…TEAD3, also known as TEF-5, is a member of the transcriptional enhancer factor family of transcription factors that promotes the transcription of a number of cell proliferation-associated genes (such as cyclins and cyclin-dependent kinases) and leads to cell cycle progression, contributing to the development of cancer and drug resistance (40,41). It is, thus, speculated that its upstream miRNAs may be tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, TEAD4 promotes cell cycle G1/S progression by increasing the expression of cyclins (D1 and E1) and CDKs (CDK2, 4, 6) ( Teng et al, 2016 ). It also augments the transcription of a lncRNA MNX1-AS1 which sequesters BCL2-targeting miR-6785-50, leading to up-regulation of pro-survival BCL2 (B-cell lymphoma 2) protein ( Shuai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%